Expanding the given expressions using Foil:
1)(–7x + 4)(–7x + 4) =
2) (–7x + 4)(4 – 7x)=
3)(–7x + 4)(–7x – 4)==
4)(–7x + 4)(7x – 4)=
The third option that is (–7x + 4)(–7x – 4) is difference of two squares.
Answer:
its D
Step-by-step explanation:
just find out what the Square root has to be plus one to equal seven
<h3>
Answer:</h3>
<u>Given equation</u> :- 6m² + 7n
where,
- <u>Constant</u> = 0.
- <u>Variable</u> = m, n.
- <u>Terms</u> = 6m² , 7n.
Answer:
Step-by-step explanation:
Finding an equation of a tangent line to that function requires that we find the derivative of the function at that point. Since this is an absolute value function with its cusp at (2, 5), the function is not differentiable here.
Answer:
measure it
Step-by-step explanation:
Greg a tape measure and measure it